Early Rehabilitation and Periprosthetic Bone Environment after Primary Total Hip Arthroplasty: A Randomized Controlled Trial. Issue 5 (2nd June 2021) - Su, RiLiGe; Feng, Wei; Liu, Xu; Song, Ya; Xu, Zhe; Liu, Jian‐guo
Abstract : Objective: To investigate whether the periprosthetic bone environment could be affected by activity during the early rehabilitation period after primary total hip arthroplasty (THA) and to evaluate the safety and efficacy of activity during the early rehabilitation period. Methods: This random clinical trial was conducted from January 2017 to July 2017. A total of 22 selected patients with advanced osteonecrosis of the femoral head (ONFH) who underwent primary unilateral THA were randomized (1:1) to a high activity level group (HA group) or a low activity level group (LA group). The HA group included nine men and two women, aged 53.18 ± 13.29 years. The LA group included five men and six women, aged 55.73 ± 11.73 years. The intervention was different postoperative daily walking distances guided by researchers: 1727.27 ± 564.08 m 0–2 months and 4272.73 ± 904.53 m 3–6 months postoperation for the HA group and 909.09 ± 583.87 m 0–2 months and 2409.09 ± 1068.13 m 3–6 months postoperation for LA group. The primary outcomes were radiographic evaluation (prosthetic stability and stress shielding based on the Engh scale) and bone mineral density (BMD) with a femoral prosthesis (individual and intergroup comparison using seven Gruen zones) at 6 months postoperatively. Secondary outcomes were set to confirm the safety and efficacy of activity during early rehabilitation, including day 1 erythrocyte sedimentation rate (ESR), day 1 hypersensitive C‐reactive protein (CRP), length of hospital stay (LOS), and the Harris hip score (HHS) at discharge, 2 months postoperatively, and 6 months postoperatively. Results: Patients were followed up for 6 months after surgery. Regarding primary outcomes, all prostheses were assessed as stable, with bone in‐growth. There were no adverse events in any cases. The HA group had a higher incidence of stress shielding than the LA group, but there was no statistical significance (63.64% vs 18.18%; P  > 0.05). The degree of stress shielding had a different distribution for the two groups ( P  < 0.05). In the HA group and the LA group, the median percentage difference of the BMD on the operated side was −25% and was −13% in Zone 1, −8% and − 1% in Zone 2, +1% and 3% in Zone 3, +6% and + 6% in Zone 4, −2% and +2% in Zone 5, −3% and −1% in Zone 6, and −24% and −12% in Zone 7 compared with the unoperated side. The BMD was significantly reduced in the medial proximal femur (Zone 1) and the lateral proximal femur (Zone 7) in both groups ( P  < 0.05). Furthermore, it was increased in the distal femur (Zone 4) in the HA group ( P  < 0.05). No difference was found in the BMD when comparing between groups. Regarding secondary outcomes, there was no statistical difference in day 1 ESR and day 1 CPR. The average LOS was similar in the HA and LA groups (7.00 days vs 7.18 days, P  > 0.05). The HHS on day of discharge was higher in the HA group than in the LA group (60.73 ± 5.37 points vs 51.18 ± 8.05 points, P  < 0.05); however, no statistically significant difference was found in postoperative the HHS at 2 months (81.73 ± 6.92 points vs 78.36 ± 9.18 points, P  > 0.05) and 6 months (90.45 ± 5.24 points vs 91.55 ± 4.03 points, P  > 0.05). Conclusion: High activity levels during early rehabilitation after primary THA accelerate the process of bone remodeling and aggravate stress shielding, with no significant benefits for functional recovery. Abstract : X‐rays of three patients with osteonecrosis of the femoral head (ONFH). Femoral collapse and acetabular arthritis were evident in preoperative X‐rays (A1, B1, and C1). Stress shielding levels of 0, 1, and 2 were apparent on X‐rays 6 months postoperatively (A2, B2, and C2).